2018
DOI: 10.1111/vox.12731
|View full text |Cite
|
Sign up to set email alerts
|

Donor InSight: characteristics and representativeness of a Dutch cohort study on blood and plasma donors

Abstract: Background and Objectives More insight into donor health and behaviour may contribute to more efficient and focused strategies regarding donor care and management. Donor InSight (DIS) is a Dutch cohort study of blood and plasma donors. We aimed to outline the objectives and methods of DIS, describe the cohort, and compare it to the active Dutch donor population. Materials and Methods In 2007‐2009 (DIS‐I, n = 31 338) and 2012‐2013 (DIS‐II, 34 826, of whom 22 132 also participated in DIS‐I) questionnaire data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 26 publications
(38 reference statements)
1
42
0
Order By: Relevance
“…Details of DIS-III have been described elsewhere and information about Hb trajectories is available in the Online Supplementary Methods . 32 …”
Section: Methodsmentioning
confidence: 99%
“…Details of DIS-III have been described elsewhere and information about Hb trajectories is available in the Online Supplementary Methods . 32 …”
Section: Methodsmentioning
confidence: 99%
“…DIS is a Dutch cohort study of blood and plasma donors carried out by Sanquin—the only organization in the Netherlands authorized to collect blood from donors [32]. The wide geographical distribution of Sanquin’s blood collection centers across the Netherlands and the large number of blood donors involved in the study yield data that allows us to explore the association of population density on lifestyle behaviors and blood lipid levels.…”
Section: Methodsmentioning
confidence: 99%
“…This sample bank was then used to investigate the prevalence of HIV‐1, HIV‐2, human T‐cell lymphotropic virus type I (HTLV‐I) and type II (HTLV‐II) seropositivity in first‐time blood donors, ascertain associated risk factors and observe the subsequent rate of seroconversion in repeat donors over time as a measure of infection incidence. Blood donor‐based biobanks have also been established in Germany , the UK , the Netherlands , Denmark , Italy and Japan and it is claimed over 200 publications in the peer‐reviewed scientific literature have resulted from such repositories . To date, these studies have mainly investigated questions related to transfusion safety such as the epidemiology and detection of TTIs , donation‐related physical symptoms and iron‐deficiency anaemia .…”
Section: Principles Of Information Disclosurementioning
confidence: 99%
“…A 2008 survey of blood services in fifteen countries revealed that operational archiving of donor specimens was usually limited to serum or plasma; however, DNA extraction was described for selected purposes, such as donors with rare red cell antigens. Subsequently, DNA isolation from blood donors specifically for the purpose of research biobanking has been described . Public opinion surveys have indicated that donors themselves are largely supportive of the contribution of their blood donation to research biobanks, even for identity‐linked genetic research …”
Section: Principles Of Information Disclosurementioning
confidence: 99%